Pengaruh Suku, Marga Dan Agama Terhadap Minat Beli Masyarakat Perspektif Ekonomi Syariah Dengan Harga Sebagai Variabel Intervening Pada Pasar Mardika Kota Ambon - Makatita, Armin Rusli (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to determine the direct effect of the variables of ethnicity, clan, religion, and price on purchase intention and to determine the indirect relationship between ethnicity, clan, and religion variables on purchasing interest through prices at the Mardika market, Ambon City, from an Islamic economic perspective. This research is a quantitative research with a descriptive approach. The data source in this study is primary data derived from questionnaires. The sample in this study were 160 people. The data processing technique used is the Structural Equation Model (SEM), where the data analysis used is the outer model analysis, inner model analysis, and hypothesis testing. The results of the study show that ethnicity influences purchase intention. Marga has an effect on buying interest. Religion influences buying interest. Prices affect buying interest. Tribe has no effect on price. Marga affects the price. Religion has no effect on prices. Tribe has no effect on buying interest through price. Marga influences buying interest through price. Religion has no effect on buying interest through price.